If we were to use the example:
∀ x ∈ Z, | x | > 0 ⇒ ∃ z ∈ Z, x < z
We would have the following steps for establishing the proof:
Assume ∀ x ∈ Z # domain assumption
Assume | x | > 0 # antecedent
Let z' = ... # some value that depends on x
[proof of z' ∈ Z]
Then, z' ∈ Z
[proof of x < z']
Then, x < z'
Then ∃ z ∈ Z, x < z # introducing ∃
Then ∀ x ∈ Z, | x | > 0 ⇒ ∃ z ∈ Z, x < z
Let's dissect these steps, separating it by their indentation. We would have, in this case, 3 indents:
Then ∀ x ∈ Z, | x | > 0 ⇒ ∃ z ∈ Z, x < z
Let's dissect these steps, separating it by their indentation. We would have, in this case, 3 indents:
- Overall proof
- If 'antecedent', then 'right-hand side statement'
- Proof of 'right-hand side statement' for limited or universal variable
If we were to work it the other way around, we would have:
- Proof that the 'right-hand side statement' holds itself true for a variable that belongs to the desired domain and scope (∃ or ∀)
- Since it was proven that the 'right-hand side statement' is true for a variable that belongs to the domain and scope, given the antecedent, we can conclude that it holds true for the desired domain
- Since it was proven with the antecedent, and the antecedent depends on the domain limitations, then the whole statement must be true.
While this was explained using several words, it is important not only to learn the structure, but also to understand why it is used in such a way.
No comments:
Post a Comment